2004
DOI: 10.1063/1.1667276
|View full text |Cite
|
Sign up to set email alerts
|

Anode/organic interface modification by plasma polymerized fluorocarbon films

Abstract: We investigated the effects of plasma polymerized fluorocarbon films (CFx) on device performance in organic light-emitting diodes (OLEDs). OLEDs with a 0.3-nm thick CFx film on an untreated indium tin oxide (ITO) anode showed identical current density–voltage characteristics and improved operational stability, as compared to the device with an ultra violet-treated ITO anode. Hole injection was virtually blocked when Au was replaced for ITO as an anode, while an ultrathin CFx film overlaid on an Au anode substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…4(a)] except the additional peaks of Au 4d and Au 4f , i.e., no modification effect on the ITO surface. Therefore, Au on ITO cannot provide better hole injection, which is agreed with [18] In summary, we show that ITO/Au/V 2 O 5 composite electrode can be used as an effective anode for bottom emitting OLEDs. Hole injection is virtually blocked when Au is added on ITO as an anode.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…4(a)] except the additional peaks of Au 4d and Au 4f , i.e., no modification effect on the ITO surface. Therefore, Au on ITO cannot provide better hole injection, which is agreed with [18] In summary, we show that ITO/Au/V 2 O 5 composite electrode can be used as an effective anode for bottom emitting OLEDs. Hole injection is virtually blocked when Au is added on ITO as an anode.…”
supporting
confidence: 57%
“…In addition, many high work function metals such as Ag and Au [14], [15] have been studied as the anode materials. However, they are not suitable for the anode as the hole injection is virtually blocked when the metal anodes are used [16]- [18]. The reports generally concluded that the performance of OLEDs with metal anodes is poorer than those OLEDs with ITO anodes.…”
mentioning
confidence: 99%
“…[2] Interface engineering between the anode and the emitting layer is important for the improvement of the device lifetime as well as luminous efficiency in PLEDs. Previous literature reports described several approaches to interface engineering that resulted in improving the device performances of organic light-emitting diodes, for instance, i) anode modification by plasma treatment, [3,4] ii) chemical modification of the anode, [5][6][7] iii) introducing a hole-injection layer (HIL), [8][9][10][11][12][13][14][15][16][17] and iv) a hole-transporting interlayer between the HIL and emitting layer. [18][19][20] Hole-injecting conducting polymer films such as polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene) (PEDOT) [10][11][12][13] on indium tin oxide (ITO) play important roles to improve the device efficiency and the stability, because they can improve the hole injection from the ITO (work function: ca.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The Helmholtz expression derived from simple electrostatics, ∆φ ) qn∆µ ⊥ / r 0 , provides the conceptual basis for many practical attempts to enable this change in work function; here, q is the elementary charge, n is the surface dipole density, ∆µ ⊥ is the dipole moment perpendicular to the surface, r is the relative dielectric constant, and 0 is the vacuum permittivity. 8 An elegant model that has been proposed 9 within this context is based on an introduced dipole layer on the surface of the ITO: 10,11 If the negative end of the surface dipole species points away from the ITO surface, the work function of ITO is increased, and the hole injection barrier is decreased.…”
mentioning
confidence: 99%